Incineration of municipal waste : specialized seminars on Incinerator Emissions of Heavy Metals and Particulates, Copenhagen, 18-19 September 1985 and Emission of Trace Organics from Municipal Solid Waste Incinerators, Copenhagen, 20-22 January 1987 - Dean, Robert B. (Academic Press Limited, 1988)
Incineration of Municipal Waste.